SITUATION OF THE GENETIC DATABASE OF VERTEBRATES OF THE LORETO REGION, PERU - ROJAS ZAMORA, Rommel Roberto (2018)
The Loreto region has the greatest geographical extension of Peru and has a mega diversity of flora and fauna that supports the development of socio-economic and cultural activities. In this study we evaluate the knowledge of the genetic database of vertebrates in Loreto. We use the gene sequence search implemented in the R rentrez package, we organize and compare the quantity of sequences in different taxonomic levels of each order of vertebrates, most used genes and existence of genetic sequences for species of commercial interest and for conservation. Our results indicate the existence of 1 960 genetic sequences deposited in the GenBank, of which 38,52% belong to the Fish; 29,33% are amphibians; 21,98% birds; 8,92% mammals and 1,22% reptiles. Our results estimates that only 19,44% of vertebrate species in Loreto have genetic data. The genes most used for these analyzes varied in abundance depending on the group of vertebrates. All species of commercial and conservation interest did not present genetic data. The general panorama of the genetic database of the Loreto region is indispensable for its integration with ecological-evolutionary studies and the elaboration of sustainable management and conservation plans.